The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/0391560321990271
|View full text |Cite
|
Sign up to set email alerts
|

Primary renal non-Hodgkin’s lymphoma: A narrative review of literature

Abstract: Renal involvement by Non-Hodgkin’s lymphoma (NHL) is very rare, and involvement of the kidney as the primary site of NHL (PRNHL) is much more uncommon. Gold standard for the diagnosis of PRNHL is histology and imaging modalities although helpful are not specific. Nephrectomy has been mostly recommended for low grade lymphomas, and for high grade PRNHLs, chemotherapy without nephrectomy has been recommended as the treatment of choice. This tumor is aggressive with poor prognosis. This poor prognosis is partly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…A systematic review of 187 primary adrenal lymphomas reported in the English literature till 2013 demonstrated that is a typically symptomatic and aggressive, high grade disease, which primarily affects elderly males and is bilateral in 70% of patients. 17 In the past two decades, a total of 83 patients of primary renal NHL lymphoma, including 17 patients with simultaneous involvement of other sites, were reported in the English literature, 18 the majority being DLBCL (n = 47), two of which were incidental findings. [19][20][21] A retrospective review of the cancer registry in Gundersen Health System from 1995 through 2014 yielded 36 patients with lymphoid neoplasms involving prostate, kidney, bladder, and penis.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 187 primary adrenal lymphomas reported in the English literature till 2013 demonstrated that is a typically symptomatic and aggressive, high grade disease, which primarily affects elderly males and is bilateral in 70% of patients. 17 In the past two decades, a total of 83 patients of primary renal NHL lymphoma, including 17 patients with simultaneous involvement of other sites, were reported in the English literature, 18 the majority being DLBCL (n = 47), two of which were incidental findings. [19][20][21] A retrospective review of the cancer registry in Gundersen Health System from 1995 through 2014 yielded 36 patients with lymphoid neoplasms involving prostate, kidney, bladder, and penis.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider nephrectomy as part of the management plan in addition to chemotherapy in unilateral PRL. 1 …”
Section: Discussionmentioning
confidence: 99%
“…However, PRL is extremely rare and comprises less than 1% of all renal masses and less than 1% of extranodal lymphomas. [1][2][3][4][5][6] Primary renal lymphoma is a distinct clinicopathological entity with highly aggressive behavior, and 50% of the cases also exhibit extrarenal involvement. 6,7 Utilizing the Surveillance, Epidemiology, and End Result )SEER( database, Taneja et al 2 and Chen et al 4 showed that diffuse large B-cell lymphoma )DLBCL( is the most common histopathological subtype.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primary renal lymphoma (PRL), one type of NHL, restricting to kidney without other organ infiltration, is extremely rare in children. [ 2 ] Given the rarity and greatly overlapped presentations with other malignant renal lesions, pediatric PRL may be easily misdiagnosed. [ 3 ] As per literature review, most of the time they were diagnosed post-surgical resection for other clinically diagnosed malignancies.…”
Section: Introductionmentioning
confidence: 99%